Assessment of the Dietary Supplements Effects on Maternal Underweight in Nigeria - Chiobi, Chukwuebuka Jude; Chiobi, Uzoamaka Angela; Omeje, Ambrose Nnaemeka; Mobosi, Ikechukwu Andrew; Ugwu, Michael Okike; Ugwu, Nnamdi Simeon (UI Scholars Hub, 2025)
Maternal underweight continues to rise and, if not properly managed, will lead to increased mortality. This contradicts the United Nations Sustainable Development Goal of reducing maternal mortality by 2050. Therefore, this study aimed to determine the probable effect of dietary supplements on maternal underweight in Nigeria. This study employed probit estimation using the maximum likelihood technique in 2022, with the 2018 Nigeria Demographic Health Survey data as the basis for analysis. The results showed a statistically significant effect of dietary supplements on maternal underweight in Nigeria. The likelihood of dietary supplements impacting maternal underweight was approximately 0.4% lower, on average, for mothers who took dietary supplements compared to those who took non-dietary supplements. That is, maternal underweight could be reduced significantly if mothers were consuming the required dietary supplements during their reproductive ages. This study concludes that the head of household age, wealth index, and mothers’ education level are likely to reduce maternal underweight. In contrast, household size is unlikely to have this effect when mothers take dietary supplements, with a very strong effect.